Cost-effectiveness of sotorasib as a second-line treatment for non-small cell lung cancer with KRASG12C mutation in China and the United States - Zhu, Ya-Ning; Tang, Meng; Sun, Ke-Xin; Gao, Bei; Shi, Xian-Peng; Zhang, Peng (Frontiers in Pharmacology, 2024)
To evaluate the cost-effectiveness of sotorasib versus docetaxel in non-small cell lung cancer (NSCLC) patients with KRAS G12C mutation from the China and United States'socialperspective.A Markov model that included three states (progression-free survival, postprogression survival, and death) was developed. Incremental cost-effectiveness ratio (ICER), quality-adjusted life-year (QALY), and incremental QALY were calculated for the two treatment strategies. One-way sensitivity analysis was used to investigate the factors that had a greater impact on the model results, and tornado diagrams were used to present the results. Probabilistic sensitivity analysis was performed with 1000 Monte Carlo simulations. Assume distributions based on parameter types and randomly sample all parameter distributions each time., The results were presented as cost-effectiveness acceptable curves.This economic evaluation of data from the CodeBreak 200 randomized clinical trial.In China, sotorasib generated 0.44 QAYL with a total cost of $84372.59. Compared with docetaxel, the ICER value of sotorasib was $102701.84/QALY, which was higher than willingness to pay(WTP), so sotorasib had no economic advantage. In the US, sotorasib obtained 0.35 QALY more than docetaxel, ICER was $15,976.50 /QALY, which was more than 1 WTP but less than 3 WTP, indicating that the increased cost of sotorasib was acceptable. One-way sensitivity analysis showed that the probability of sotorasib having economic benefits gradually increased when the cost of follow-up examination was reduced in China. And there was no influence on the conclusions within the range of changes in China. When the willingness to pay(WTP) exceeds $102,500, the probability of sotorasib having cost effect increases from 0 to 49%.Sotorasib had a cost effect from the perspective in the United States. However, sotorasib had no cost effect from the perspective in China, and only when the WTP exceeds $102,500, the probability of sotorasib having cost effect increases from 0 to 49%.